Meteorological and physical conditions of Salt Pan Areas with Filtering-Threaded Technology (TUF) in Cirebon Regency, Indonesia - Rikha Bramawanto; Sophia L. Sagala (Pusat Riset Kelautan, 2016)
Salt pans in Indonesia are commonly set in batch operation and highly depend on the meteorological condition. Moreover, the common salt pans are considerably limited in the area (averagely 0.5-1 Ha) as it is not organized by industries or governments; local farmers instead. However, with such confinement, there are some salt pans particularly with filtering-threaded technology system (TUF system) that successfully produce salt with high production (>100 tons/Ha/season) and grade-1 quality. The present study was aimed to get insight on the meteorological condition at the salt pans using TUF system and the physical condition of the sea brine obtained from the TUF in the local salt pans in Cirebon Regency. Measurements on temperatures (air, brine and soil), humidity, wind direction and speed, brine conductivity, brine density and salinity were conducted at the pre-crystallizer pond, brine storage pond, channels, the condenser, and the reservoir. The meteorological parameters were recorded hourly using Automatic Weather Station and the data were taken during 49 hours ly, from August 26-28, 2014 started at 04.00 pm. Meanwhile, the physical parameters of the brine were measured every three hours using water quality meter. The results showed that the meteorological condition, brine physical condition, and the process occurred during salt production were still in agreement and met the theoretical condition or modeling. Even though the relative humidity and some wind speed in the present study area were out of the standard criteria recommended (5m/s for wind speed), the study showed that salt still can be produced in condition of relative humidity (52-88%), wind speed (0.2-5.7 m/s), and ambient temperature (23.2-32.4 oC). Interestingly, it is found that brine thickness and volume could be adjusted to get an optimum temperature of brine (reached 36.2 oC), in order to enhance the evaporation process. The highest soil temperature (34.7 oC) was found at 15.00 in the pre-crystallizer ponds. Meanwhile, the lowest temperature (26.7oC) was found early morning at 04.00 in the reservoir pond. Brine in the pre-crystallizer had highest thermal storage capacity during daytime (06.00-16.00), whereas soil in the pre-crystallizer tended to store heat during the nighttime (18.00-22.00). Brine and soil temperature fluctuation indicate that solar irradiation and convection process transferring heat energy from soil to brine occurs and also took an important part in the evaporation process. It therefore can be concluded that by understanding the condition of meteorology at the salt pan areas and the brine characteristic obtained, the appropriate technology resulting high-quality and quantity salt production could be devised.